State, religion, and Muslims : between discrimination and protection at the legislative, executive, and judicial levels - Bahçecik, Şerif Onur,; Saral, Melek, (Muslim Minorities;, 2020)
"State, Religion and Muslims: Between Discrimination and Protection at the Legislative, Executive and Judicial Levels brings together the academics from different academic disciplines and offers an in-depth analysis of discrimination against Muslims in western countries affecting them in specific areas of life. The volume provides a comprehensive look at the legislative, executive and judicial dimensions of discrimination across the 12 Western countries situating discriminatory practices in their institutional framework with a multidisciplinary look. Exploring the most formidable aspects of the discrimination against Muslims - education, employment, exercise of religion, state relations with religious communities and hate crime and hate speech - the volume illustrates that the individual, structural and institutional discrimination against Muslims living in western countries has become a routine".